2020
DOI: 10.3390/healthcare8040371
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Country Dietary Habits Using Machine Learning Techniques in Relation to Deaths from COVID-19

Abstract: COVID-19 disease has affected almost every country in the world. The large number of infected people and the different mortality rates between countries has given rise to many hypotheses about the key points that make the virus so lethal in some places. In this study, the eating habits of 170 countries were evaluated in order to find correlations between these habits and mortality rates caused by COVID-19 using machine learning techniques that group the countries together according to the different distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The research findings stated that countries with the highest death ratio were those who had a high consumption of fats, while countries with a lower death rate have a higher level of cereal consumption followed by a lower total average intake of kilocalories (García-Ordás, et al (2020)). A study conducted to (Shinwoo et al 2020) their research data were extracted from the immigrant Korean COVID-19 patients who were 290 cases from 12 states all of them older than 18 years, the study observed the ability to the prediction of discrimination-related variables, such as racism effects, and sociodemographic factors that influence the psychological distress level during the COVID-19 pandemic, they nominated the supervised learning as the method and then using the Artificial Neural Network ANN as the main algorithm, their result showed The Artificial Neural Network (ANN) analysis, which is a statistical model and able to examine complex non-linear interactions of variables, was applied.…”
Section: Discussionmentioning
confidence: 92%
“…The research findings stated that countries with the highest death ratio were those who had a high consumption of fats, while countries with a lower death rate have a higher level of cereal consumption followed by a lower total average intake of kilocalories (García-Ordás, et al (2020)). A study conducted to (Shinwoo et al 2020) their research data were extracted from the immigrant Korean COVID-19 patients who were 290 cases from 12 states all of them older than 18 years, the study observed the ability to the prediction of discrimination-related variables, such as racism effects, and sociodemographic factors that influence the psychological distress level during the COVID-19 pandemic, they nominated the supervised learning as the method and then using the Artificial Neural Network ANN as the main algorithm, their result showed The Artificial Neural Network (ANN) analysis, which is a statistical model and able to examine complex non-linear interactions of variables, was applied.…”
Section: Discussionmentioning
confidence: 92%
“…The latter [ 28 ] and hyperinsulinemia [ 70 ] play a crucial role in thrombo-inflammation during COVID-19 infection. Countries with higher and lower death rates for COVID-19 appear to have high consumptions of fats and cereal, respectively [ 71 ]. Hyperglycemia and Reactive Oxygen Species (ROS)-induced oxidation of carbohydrates generate the adduct derivatives advanced glycation end products (AGE) [ 72 ].…”
Section: Diabesity Meta-inflammation and Il-6: The Role In Severmentioning
confidence: 99%
“…Various aspects of this pandemic are data-driven, including infection diagnosis based on CT scans of patients [ 1 , 2 ] or other symptoms [ 3 ], infection diagnosis based on metabolomics [ 4 ] and serologic data [ 5 , 6 ], epidemiologic analysis [ 7 , 8 ] and predictions [ 9 ], viral genetics [ 10 ] and host epigenetics studies [ 11 ], evolutionary path discovery [ 12 ], contact tracing [ 13 ] and quarantine enforcing [ 13 ], and numerous other aspects [ 14 ].…”
Section: Introductionmentioning
confidence: 99%